Casein hydrolysate's effects on the fermentation properties, texture, and chemical characteristics and the bacterial microbiota of fermented glutinous rice dough - Guo, Ling; Liu, Biqi; Jiang, Yujun; Zhang, Wei; Han, Jing; Qu, Wenxuan; Han, Yuxi; Zhao, Xinhuai; Yang, Xinyan (Frontiers in Microbiology, 2023)
To investigate how casein hydrolysate affected the physicochemical properties and microbiological diversity of the glutinous rice dough (natural fermentation and yeast fermentation), we analyzed its fermentation properties, carbohydrate, protein degradation, texture, and bacterial composition. According to the findings, casein hydrolysate increased the total LAB number, as well as organic acid content, in naturally fermented and yeast fermented glutinous rice dough by 3.59 and 8.19%, respectively, and reduced the fermentation time by at least 2 h. Meanwhile, casein hydrolysate enhanced the content of reducing sugars by 4.46 and 13.53% and increased protease activity by 29.9 and 27.7%. In addition, casein hydrolysate accelerated protein breakdown and regulated the hardness of the dough to improve the texture. Casein hydrolysate enriched the bacterial richness and diversity of dough. After adding casein hydrolysate, it promoted the growth of Pediococcus, Enterococcus, Lactobacillus, and Streptococcus. According to the Spearman correlation analysis, environmental factors (pH, lactic acid, acetic acid, reducing sugar content, and protease activity) exhibited the major driver for the abundance of bacterial species (Spearman correlation coefficient: −0.71 to 0.78). As a potential food additive, casein hydrolysate can improve the fermentation and quality of glutinous rice dough, increase consumer acceptance of cereal foods, and give consumers healthier options.